Generation and Characterization of Germline-Specific Autophagy and Mitochondrial Reactive Oxygen Species Reporters in Drosophila - Nilangekar, Kiran; Murmu, Nidhi; Sahu, Govind; Shravage, Bhupendra V. (Frontiers in Cell and Developmental Biology, 2019)
Oogenesis is a fundamental process that forms the egg and, is crucial for the transmission of genetic information to the next generation. Drosophila oogenesis has been used extensively as a genetically tractable model to study organogenesis, niche-germline stem cell communication, and more recently reproductive aging including germline stem cell aging. Autophagy, a lysosome-mediated degradation process, is implicated in gametogenesis and aging. However, there is a lack of genetic tools to study autophagy in the context of gametogenesis and germline stem cell aging. Here we describe the generation of three transgenic lines mCherry-Atg8a, GFP-Ref(2)P and mito-roGFP2-Orp1 that are specifically expressed in the germline compartment including germline stem cells during Drosophila oogenesis. These transgenes are expressed from the nanos promoter and present a better alternative to UASp mediated overexpression of transgenes. These fluorescent reporters can be used to monitor and quantify autophagy, and the production of reactive oxygen species during oogenesis. These reporters provide a valuable tool that can be utilized in designing genetic screens to identify novel regulators of autophagy and redox homeostasis during oogenesis.